ETHNOMEDICINAL USES IN SCORPION POISONING (GONUSU VISHA) IN SRI LANKAN TRADITIONAL MEDICINE - Ediriweera, *E.R.H.S.S.; Ratnasooriya, W. D.; Kamathewatta, K. W. M. D. (International Journal of Ayurveda and Pharma Research, 2018)
Scorpions use their sting as a defensive weapon or as a mechanism to incapacitate prey. The scorpion sting possesses venom and the character of the poison depends on the scorpion species. Some may lead to death. Ayurveda and Sri Lankan traditional physicians treat scorpion sting by administering medicines internally and externally, in various forms. Data was gathered from Ayurveda and Sri Lankan traditional medical books, through interviewing physicians, research journals and internet. Herbs, minerals and animal sources are used to treat scorpion sting. Analgesic, anti-inflammatory, antihistaminic, antipyretic, antispasmodic, antioxidant, cardioproective, respiratory protective, neuroprotective properties and anti-scorpion venom activity of these ingredients are scientifically proven. Due to these properties, these ingredients are capable of overcoming the symptoms such as pain, swelling, redness, itching, spasms, neurotoxicity and also cardiac and respiratory failure occurring through scorpion sting. It is concluded that Ayurveda and Sri Lankan traditional physicians possess multi-faceted, effective treatment methods for scorpion stings which can be scientifically proven.